Analisis usaha pengolahan amplang di Kecamatan Sanga-Sanga Kabupaten Kutai Kartanegara: Analysis of amplang processing business at Sanga-Sanga District Kutai Kartanegara Regency - Gusti Haqiqiansyah; Dayang Diah Fidhiani; Zul Asman Randika (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2022)
This study was aimed to analyze the prospects of development of the financial aspects of amplang processing and marketing channel of amplang processing business. The data was collected through a survey, completed by direct observation in the field and interviews with the respondents. The applied data analysis includes analysis of costs, revenues, income and business feasibility. The results showed the average revenue earned from amplang processing business is Rp. 7.040,000 per month or Rp. 70.400,000 per year, while the average cost of Rp. 4.623.167 per month or Rp. 46.238.333/year. The average income was found as much as Rp. 2.416.167/month or Rp. 24,161,667 / year. The value of the balance of revenue and cost (R/C) in the business of processing amplang is 1.54, which means that the amplang processing business is able to provide a gain of 1.54 of the cost. There are two pattern of marketing channel that were identified in the field, the first pattern is: amplang producer to retailer to consumer; and the second pattern is: amplang producer to consumer directly.